On the spider genus Syspira Simon, 1895 (Araneae: Miturgidae) in the Caribbean: four new species from Dominican Republic - Brescovit, Antonio D.; Sánchez-Ruiz, Alexander; Bonaldo, Alexandre B. (Zootaxa, 2018)
Four new species of Syspira Simon, 1895 are described: Syspira cimitarra sp. nov., Syspira jimmyi sp. nov., Syspira medialuna sp. nov. and Syspira agujas sp. nov., all endemic in the Dominican Republic.